SISTEM MANAJEMEN PROTEKSI MOTOR RELAY GE MULTILINE 269 PLUS PADA MOTOR FORCED DRAFT FAN DI PT. INDONESIA POWER PGU SURALAYA - Mastiri Mastiri; Desmira Desmira (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
Electrical energy continues to grow over time, power plants with large capacities are the main sources of electricity in Indonesia, one of which is the Steam Power Plant (PLTU). In the field of power plants that use coal always need air during the electricity production process. This study aims 1) to determine the protection management system on the Forced Draft fan motor using GE Multilin 269 Plus, 2) Setting GE Multilin 269 Plus as protection, 3) The results of the protection in the form of Normal Motor, Alarm, and Trip conditions in the accumulation of imbalance (Unbalance) ). The method used is a quantitative research method based on analysis, taking data and then analyzing the data obtained. The results of this quantitative study regarding the Unbalance value or imbalance of the electric motor analyzed resulted in a value of 5.8% for normal conditions, 10.86% for alarm conditions on multilin and 15.50% in trip conditions or the motor had stopped. These values ​​are obtained from the results of calculations comparing negative sequence currents and positive sequence currents (In/Ip). The conclusion obtained is that the GE Multilin 269 Plus protects the electric motor from system damage by using a current sensor and through a setting point that is adjusted to the provisions of NEMA (National Electrical Manufacturers Association) with an unbalance value of more than 15% for trips, more than 10% for alarm conditions and less than 10% under normal conditions